Kontribusi Fasilitator Pendamping dalam Meningkatkan Akses Pasar Bagi Pelaku UMKM Nasabah BTPN Syariah Kecamatan Tandes Suarabaya - Dynda Sovia Ardhita; Jojok Dwiridotjahjono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The research entitled "Kontribusi Fasilitator Pendamping dalam Meningkatkan Akses Pasar bagi Pelaku UMKM Nasabah BTPN Syariah Kecamatan Tandes Surabaya " discusses the role of facilitators in expanding market access for MSMEs customers of Bank BTPN Syariah in Surabaya. This study aims to help MSMEs players understand the importance of preparing marketing strategies to maximize the scope of their business. The method used is a qualitative approach with descriptive methods. The data collection technique used was interviews conducted naturally and conducting a SWOT analysis on each MSMEs customer of BTPN Syariah. The research results show that the role of companion helps BTPN Syariah MSMEs customers to maximize sales. Having an accompanying facilitator for MSMEs players can help in developing effective business strategies, market understanding, marketing and better financial management.